Argument in Favor of Sexual Work and Ethical Implications - Gimeno Presa, MÂª Concepción (Opinión Jurídica, 2018)
How modern democratic states should deal with the practice of prostitution is now a controversial issue. Within the feminist movement, the way to solve this problem has created a gap that seems difficult to solve. Advocates of governments regularizing prostitution as an additional employment relationship justify their position with arguments that they consider legally solid and ethically neutral. They claim that the reasons given for prohibiting prostitution and not considering it as a work activity are moral reasons. In turn, they argue that democratic states governed by the rule of law do not have the function of imposing ethical beliefs on their citizens but of safeguarding their rights, especially the right to individual freedom. In this work, arguments for and against that prostitution should be regularized as a work Re mentioned and show how the reasoning of the representatives of feminism in favor of sex work is built on an ethical theory that is assumed to be valid and therefore not the object of discussion. I state that the most appropriate way to reach a consensus on this issue would be to openly and in advance of the political and legal debate, raise an ethical reflection on what postulates and what moral conception of sexuality seem to us to be the most valuable concept in dealing with this complex problem.